1997
DOI: 10.1002/(sici)1099-078x(199707)12:3<113::aid-brt170>3.3.co;2-6
|View full text |Cite
|
Sign up to set email alerts
|

Applying behavioral theory to practice: an examination of the behavioral momentum metaphor

Abstract: This paper discusses some of the difficulties that arise in the practical applications of theories derived from specific experimental settings. Nevin's metaphoric extension of the physical concept of momentum to modifying behavior (i.e., behavioral momentum) is used as a recent example. Problems in the application of behavioral momentum are discussed, alternative analyses are offered, and methods for further testing the process are suggested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…The results of a series of studies have shown that compliance to low-p requests was enhanced when those requests were preceded by the completion of several brief, highly preferred requests/activities (Davis & Reichle, 1996;Horner, Day, Sprague, O'Brian, & Heathfield, 1991;Mace et al, 1988). Although the mechanism responsible for the effects of high-p sequences is the subject of debate (see Brandon & Houlihan, 1997;Houlihan & Brandon, 1996;Nevin, 1996, for discussion), research indicates that the intervention is effective at increasing compliance across a variety of settings and behaviors.…”
mentioning
confidence: 99%
“…The results of a series of studies have shown that compliance to low-p requests was enhanced when those requests were preceded by the completion of several brief, highly preferred requests/activities (Davis & Reichle, 1996;Horner, Day, Sprague, O'Brian, & Heathfield, 1991;Mace et al, 1988). Although the mechanism responsible for the effects of high-p sequences is the subject of debate (see Brandon & Houlihan, 1997;Houlihan & Brandon, 1996;Nevin, 1996, for discussion), research indicates that the intervention is effective at increasing compliance across a variety of settings and behaviors.…”
mentioning
confidence: 99%
“…Debate exists concerning whether the abovementioned technique is consistent with laboratory models of behavioral momentum (Brandon & Houlihan, 1997;Nevin, 1996;Plaud & Gaither, 1996). Nevertheless, it was derived from the theory and has interesting implications for clinical work.…”
Section: Compliance With Instructionsmentioning
confidence: 99%
“…With respect to efficiency of procedural variations, multiple studies have demonstrated that a larger ratio of maintenance tasks within a task interspersal session results in less efficient acquisition of the target task (Cooke & Reichard, 1996;Nicholson, 2013;Rapp & Gunby, 2016). Some researchers have also hypothesized that task interspersal may facilitate better discrimination ability, as the client must attend to and differentiate the alternating discriminative stimulus between tasks (Brandon & Houlihan, 1997;Dunlap & Koegel, 1980;Rowan & Pear, 1985). This reasoning suggests that programming the interspersal of tasks from different domains may be preferential over tasks from similar domains.…”
mentioning
confidence: 99%